Pengaruh Proses Rekrutmen dan Seleksi Terhadap Kinerja Karyawan pada PT Akuntata Prima Consulting - Rahma, Aulia (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to examine the influence of the recruitment and selection process on employee performance at PT Akuntata Prima Consulting, a company engaged in Management Services and Registered Tax Consulting. This research uses a quantitative method with multiple linear regression tests. The results of the t-test between the recruitment and selection process and employee performance at PT Akuntata Prima Consulting show that both processes have a positive and significant effect on employee performance. Meanwhile, the F-test results indicate that the calculated F value is 21.973, with a significance value of 0.000 (less than 0.05), meaning that the recruitment and selection variables collectively influence employee performance at PT Akuntata Prima Consulting. The coefficient of determination test results show that the R Square value is 0.571 (57.1%), which means that 57.1% of the independent variables (recruitment and selection) affect the dependent variable (employee performance), while 42.9% is influenced by other independent variables not included in this study.